Childhood adversity increases the risk of onward transmission from perinatal HIV-infected adolescents and youth in South Africa. (May 2018) - Kidman, Rachel; Nachman, Sharon; Dietrich, Janan; Liberty, Afaaf; Violari, Avy
Abstract: Repeated exposure to childhood adversity (abuse, neglect and other traumas experienced before age 18) can have lifelong impacts on health. For HIV-infected adolescents and youth, such impacts may include onward transmission of HIV. To evaluate this possibility, the current study measured the burden of childhood adversity and its influence on risky health behaviors among perinatally-infected adolescents and youth. We surveyed 250 perinatally-infected adolescents and youth (13–24 years) receiving care in Soweto, South Africa. Both male and female participants reported on childhood adversity (using the ACE-IQ), sexual behavior, and psychosocial state. Viral load was also abstracted from their charts. We used logistic regressions to test the association between cumulative adversity and behavioral outcomes. Half the sample reported eight or more adversities. Overall, 72% experienced emotional abuse, 59% experienced physical abuse, 34% experienced sexual abuse, 82% witnessed domestic violence, and 91% saw someone being attacked in their community. A clear gradient emerged between cumulative adversities and behavioral risk. Having experienced one additional childhood adversity raised the odds of risky sexual behavior by almost 30% (OR 1.27, 95% CI 1.09–1.48). Viral suppression was poor overall (31% had viral loads >400 copies/ml), but was not related to adversity. Adversity showed a robust relationship to depression and substance abuse. Childhood adversity is common, influences the current health of HIV-positive adolescents and youth, and puts their sexual partners at risk for HIV infection. Greater primary prevention of childhood adversity and increased access to support services (e.g., mental health) could reduce risk taking among HIV-positive adolescents and youth.